IV International Conference “Condensed Matter and Low-Temperature Physics 2024” (CM&LTP 2024) - Hurova, D.; Dolbin, O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
From June 3 to 7, 2024, the IV International Scientific Conference “Condensed Matter and Low Temperature Physics 2024 (CM&LTP 2024)” was held online at the B. I. Verkin Institute for Low Temperature Physics and Engineering, with the participation of researchers from institutions of the National Academy of Sciences of Ukraine, the Ministry of Education and Science of Ukraine, and foreign scientists. The conference facilitated close scientific communication and the exchange of ideas between highly qualified researchers, experts in the fields of low-temperature physics, condensed matter physics, material science, nanophysics, and molecular physics, as well as young scientists. The conference program covered relevant areas of modern experimental and theoretical condensed matter physics, including low-temperature physics, superconductivity, magnetism, optics, nanophysics, biophysics, materials science, and related topics. CM&LTP 2024 served as a platform for scientists to share their knowledge, exchange new information and ideas, and find collaborators for joint projects.